Proceedings of the 13th Annual Conference on Genetic and Evolutionary Computation 2011
DOI: 10.1145/2001576.2001821
|View full text |Cite
|
Sign up to set email alerts
|

Multiple objective optimisation applied to route planning

Abstract: This paper presents an evaluation of the benefits of multiobjective optimisation algorithms, compared to single objective optimisation algorithms, when applied to the problem of planning a route over an unstructured environment, where a route has a number of objectives defined using real-world data sources.The paper firstly introduces the problem of planning a route over an unstructured environment (one where no predetermined set of possible routes exists) and identifies the data sources, Digital Terrain Eleva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…They also stressed that the entire process of data quality control should be systematised and that it should include assessment and quality description stored in metadata. Waldock and Corne (2011) have explored the possibility of cross-country vehicle movement prediction on unstructured open source spatial data using multi-criteria optimisation. Horttanainen and Virrantaus (2004) concluded that uncertainty in data accuracy should be noted throughout the modelling process, and the final user, as the decision maker, should be informed of the level of data inaccuracy.…”
Section: Physicalgeographic Factors Of Terrain Trafficability Of Milimentioning
confidence: 99%
See 1 more Smart Citation
“…They also stressed that the entire process of data quality control should be systematised and that it should include assessment and quality description stored in metadata. Waldock and Corne (2011) have explored the possibility of cross-country vehicle movement prediction on unstructured open source spatial data using multi-criteria optimisation. Horttanainen and Virrantaus (2004) concluded that uncertainty in data accuracy should be noted throughout the modelling process, and the final user, as the decision maker, should be informed of the level of data inaccuracy.…”
Section: Physicalgeographic Factors Of Terrain Trafficability Of Milimentioning
confidence: 99%
“…All models of vehicle terrain trafficability want to reproduce (in different ways) how overall ground elements slow down the vehicle in relation to its maximum predicted speed (Ahlvin and Haley, 1992). The Heuristic Approach (Waldock and Corne, 2011) of trafficability modelling based on the dynamic mathematical models of the Army Material Command Mobility Model (AMC) and the NATO Reference Mobility Model (NRMM) (Hohmann et al, 2013) were limited by their many input parameters and a multitude mathematical formulas, which made it more difficult for the end users. The invention and development of new computer technologies in the late 1980s enabled implementation of mathematical models into GIS.…”
Section: Modelling/structuring Of Physical-geographic Factors Of Terrmentioning
confidence: 99%
“…In this study this method , however when the aggregation causes the landscape to be severe and complex, treating the problem as a multiobjective one can achieve better solutions. This is a commonly observed phenomenon [9,47] and several authors have even reformulated single objective problems so they can be solved using multiobjective methods [19,24,27].…”
Section: Expected Improvement Versus Probability Of Feasibilitymentioning
confidence: 99%
“…Research works on MOEA/D generally falls into several aspects. For example, combining MOEA/D with other nature inspired meta-heuristics [8][9][10][11] , investigating on the decomposition approaches [12][13][14] , refining the weight vectors for scalar optimization subproblems [15][16][17] , changing the offspring reproduction methods in MOEA/D [18][19][20] , applying MOEA/D on benchmark and real-world problems [21][22][23][24] , and so on. In MOEA/D, the target MOP is decomposed into a set of scalar optimization subproblems by using conventional aggregation approaches.…”
Section: Introductionmentioning
confidence: 99%